Profane Illumination: On the Racial Limits of Documentary Realism - Rizvana Bradley (Film-Philosophy)
This article discusses Göran Olsson’s 2014 documentary film, Concerning Violence: Nine Chapters of the Anti-Imperialistic Defense. The film’s handling of a continental archive has gone relatively unexamined and has indeed been neglected, given how ambitious Olsson’s documentary is in terms of the breadth of its coverage of African resistance struggles across the continent. This article examines whether and how Olsson’s documentary, in its piecing together of found footage of or pertaining to 1960s and 1970s anticolonial movements, expresses an instance of the cinema becoming yet another apparatus for the reinstantiation of the absences and distortions of the archive. Though the aesthetic strategies the film deploys experiment with and expand upon a conventional documentary realist approach, the racially gendered images of the colonized that unfold from the documentary footage that comprises Concerning Violence are images which unsettle, exceed, and interrogate even the most radically reflexive tendencies of the film’s documentary realism. Ultimately, what we find in Concerning Violence are irruptions, in and through the film’s stylistic composition of image and sound, that are exorbitant to the documentary enterprise that seeks to capture them.